Immune-Inspired Framework for securing Hybrid MANET - Yasir Abdelgadir , Mohamed; Azween, Abdullah
A malicious node in mobile ad hoc networks (MANETs) can falsify a route advertisement, overwhelming traffic without forwarding it, helps in forwarding corrupted data, and injecting of false or uncompleted information. Mapping immune system security mechanisms to networking security can powerfully contribute in securing MANETs, since both are sharing some similar features because of the distributability environment in each. In a step for providing secured and reliable broadband services, formal specification logic along with a novel Immuneinspired security framework (I2MANETs) have been introduced. The different immune components synchronized to the framework through an agent that has the ability to replicate, monitor, detect, classify, and block/isolate the corrupted packets and/or nodes in a federated domain. The framework functions as the Human Immune System in: first response, second response, adaptability, distributability, survivability and other immune features. The I2MANETs can basically installed in one node in the domain, then automatically spread to the rest of the domain.